2011
DOI: 10.1002/jor.21566
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical interbody constructs: effect of a repetitive compressive force on the endplate

Abstract: Graft subsidence following anterior cervical reconstruction can result in the loss of sagittal balance and recurring foraminal stenosis. This study examined the implant-endplate interface using a cyclic fatigue loading protocol in an attempt to model the subsidence seen in vivo. The superior endplate from 30 cervical vertebrae (C3 to T1) were harvested and biomechanically tested in axial compression with one of three implants: Fibular allograft; titanium mesh cage packed with cancellous chips; and trabecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
0
24
1
1
Order By: Relevance
“…In the n-HA/PA66 group, the final rate of severe cage subsidence was 6 %, which was significantly lower than the TMC group. The risk factors related to the development of subsidence of the cages are varied, including not only intraoperative end-plate preparation and osteoporosis but also cage material and cage shape [14,21,22]. The titanium mesh cage has sharp footprints designed to anchor the cage into the adjacent endplates and avoid a translation; however, the sharp footprints lead to a smaller cage-endplate interface contact area, increasing the cutting and penetration from the cage into the vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…In the n-HA/PA66 group, the final rate of severe cage subsidence was 6 %, which was significantly lower than the TMC group. The risk factors related to the development of subsidence of the cages are varied, including not only intraoperative end-plate preparation and osteoporosis but also cage material and cage shape [14,21,22]. The titanium mesh cage has sharp footprints designed to anchor the cage into the adjacent endplates and avoid a translation; however, the sharp footprints lead to a smaller cage-endplate interface contact area, increasing the cutting and penetration from the cage into the vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical studies have shown that adding an end ring onto the conventional TMC could be beneficial by expanding the contact area between the endplate and the TMC, which can decrease the stress concentration and distribute the load from the cephalad more evenly across the endplate [16,21,24]. However, high rates of TMC subsidence were still observed in long-term follow-up studies of ACCF despite the enlarged contact area of the end surface [4,28,29], suggesting that a simple, flat end ring could not effectively prevent subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, high rates of TMC subsidence were still observed in long-term follow-up studies of ACCF despite the enlarged contact area of the end surface [4,28,29], suggesting that a simple, flat end ring could not effectively prevent subsidence. When performing compression tests, previous biomechanical works assumed that the endplate was parallel to the end of the TMC and did not consider that the endplate has a gradient under physiological conditions [16,21,24]. Therefore, these studies may artificially increase the true contact area and exaggerate the effect of a flat end ring on the compressive load.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations